2021
DOI: 10.3390/ijerph18063312
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Population-Based Cancer Screening Performance at Primary Healthcare Institutions in China

Abstract: Background: For a decade, most population-based cancer screenings in China are performed by primary healthcare institutions. To assess the determinants of performance of primary healthcare institutions in population-based breast, cervical, and colorectal cancer screening in China. Methods: A total of 262 primary healthcare institutions in Tianjin participated in a survey on cancer screening. The survey consisted of questions on screening tests, the number of staff members and training, the introduction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…On average, each institution performs annually approximately 2000, 2000 and 3000 screenings for breast, cervical and colorectal cancer, respectively. 27 Each cancer screening takes approximately 10 min for a healthcare provider. A previous survey showed that there are 206 (urban: 81; rural: 125), 231 (urban: 82; rural: 149) and 261 (urban: 95; rural: 166) primary healthcare institutions that perform breast, cervical and colorectal cancer screening in Tianjin, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, each institution performs annually approximately 2000, 2000 and 3000 screenings for breast, cervical and colorectal cancer, respectively. 27 Each cancer screening takes approximately 10 min for a healthcare provider. A previous survey showed that there are 206 (urban: 81; rural: 125), 231 (urban: 82; rural: 149) and 261 (urban: 95; rural: 166) primary healthcare institutions that perform breast, cervical and colorectal cancer screening in Tianjin, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A previous survey showed that there are 206 (urban: 81; rural: 125), 231 (urban: 82; rural: 149) and 261 (urban: 95; rural: 166) primary healthcare institutions that perform breast, cervical and colorectal cancer screening in Tianjin, respectively. 27 …”
Section: Methodsmentioning
confidence: 99%
“…The concept of community healthcare [109] is deployed with the help of a network which covers a local community. This may include a residential building, a hospital, or a rural commune.…”
Section: Community Healthcarementioning
confidence: 99%